Inhibition of hepatitis C virus gene expression by adenoviral vectors encoding antisense RNA in vitro and in vivo - González-Carmona, María Á.; Vogt, Annabelle; Heinicke, Thomas; Quasdorff, Maria; Hoffmann, Per; Yildiz, Yildiz; Schneider, Carlo; Serwe, Matthias; Bartenschlager, Ralf; Sauerbruch, Tilman; Caselmann, Wolfgang H. (Journal of hepatology, 2011)
Background & Aims - In this study, adenoviral vectors encoding an antisense RNA complementary to the 5′ non-coding region (5′NCR) of the HCV-genome were generated to inhibit HCV-RNA gene expression in cell culture and in vivo. - Methods - First and second-generation (with E4-deletion) adenoviruses encoding the HCV5′NCR in antisense direction (Ad-NCRas and Ad-E4del-NCRas) were generated. Inhibition of HCV gene expression was analyzed in hepatoma cells stably transfected with the HCV5′NCR cDNA fused to the firefly luciferase gene (NCRluc), as well as in the HCV subgenomic replicon (genotypes 1b and 2a) and the fully infectious HCV JFH-1 cell culture systems. For in vivo experiments, an adenovirus encoding the NCRluc-gene was injected intravenously to achieve a NCR-dependent luciferase-expression in the liver of C3H/HeNcrl-mice. - Results - Forty eight hours after transduction with GFP-encoding adenoviruses, >85% of HepG2-, CCL13-and Huh7-cells expressed GFP. Surprisingly, GFP-expression of E4-deleted adenoviruses was considerably reduced at the same MOI. Using antisense first-generation adenoviruses (Ad-NCRas), a significant inhibition of the 5′NCR-dependent HCV-gene expression (54±19% in HepG2-cells and 66.2±15% in Huh7-cells) was achieved 48h after transduction. In Huh7-cells containing the HCV subgenomic replicons and in infectious HCV JFH-1 cell cultures, adenovirus-mediated transcription of antisense 5′NCR significantly blocked HCV-replication (40% and 76%, respectively). Corresponding to low transgene expression, the maximal inhibition reached with Ad-delE4-NCRas was 30%. In vivo, antisense adenoviral vectors also showed a significant inhibition (40%) of NCR-dependent luciferase expression compared to control adenoviruses (p<0.05). - Conclusions - The data indicate that HCV gene expression can be inhibited by antisense RNA encoding adenoviruses in the tested settings.
Available online 30 November 2010
Gesehen am 07.07.2022